Construction Research Congress 2012 2012
DOI: 10.1061/9780784412329.050
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Spool Fabrication Sequencing by Automated Planning

Abstract: Construction of Industrial facilities involves a substantial amount of piping. Pipe spools are usually pre-fabricated from a number of raw pipes and pipe fittings (e.g. elbows, flanges, tees, etc.) in fabrication shops. Pipe spool fabrication is often affected by various disruptions from within or outside the shops. Previous research mainly focuses on shop layouts, dispatching rules, buffer location and standardized products. Another critical factor, the sequencing of pipe spool fabrication, is usually overloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Due to the complicated shapes of industrial assemblies and the limited capacity of transportation vehicles, successful delivery of materials on construction sites becomes a very challenging task. The incurred inaccuracies and defects are sometimes unpreventable due the challenging fabrication and transportation phases (Hu and Mohamed 2012).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complicated shapes of industrial assemblies and the limited capacity of transportation vehicles, successful delivery of materials on construction sites becomes a very challenging task. The incurred inaccuracies and defects are sometimes unpreventable due the challenging fabrication and transportation phases (Hu and Mohamed 2012).…”
Section: Problem Statementmentioning
confidence: 99%
“…Recently, research studies have been attempted to improve the quality of fabricated pipe spool assemblies using simulation (Hu and Mohamed 2012;. Having simulated the fabrication process, the users are able to identify the conflicting processes using different scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…pipe spool fabrication system). 19 . It is indicated that none of the AI planners are fully adequate to solve real-life pipe spool fabrication sequencing problems.…”
Section: Application Of Pddl To Pipe Spool Fabrication Sequencing Promentioning
confidence: 99%
“…Example domain and problem definition files for pipe spool fabrication (Di and Mohamed 2012)19 A number of experiments are conducted to test the capability of AI planners to solve the pipe spool fabrication sequencing problem. These experiments are designed to be of incremental complexity.…”
mentioning
confidence: 99%